Innovation in Islamic Education Curriculum Development - An Interdisciplinary Approach - Akbar, Muhammad Bintang; Heri, Totong (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
The need for an educational curriculum that is adaptive to the development of the times is increasingly urgent. Responding to the ever-changing demands of modernization while still upholding strong and relevant Islamic ideals is difficult for Islamic education. An interdisciplinary approach in curriculum development is one of the tactical improvements that can be used; He balances the integration of general science and religious science. This method seeks to harmonize the two to give students a thorough understanding. In addition, this method is expected to produce up-to-date and flexible education to the times and prepare students to face various global problems. Using a literature review, this study investigates how interdisciplinary ideas such as curricular integration, the creation of creative teaching strategies, and the use of technology in the classroom are applied in Islamic education. The study's findings show that an interdisciplinary approach can improve the application of Islamic education by equipping students to become competitive, critical, and creative human beings in the global era. In addition, this research significantly advances the creation of an inclusive and progressive Islamic education curriculum and can serve as a valuable resource for education officials.